Business cycle asymmetries and the labor market - Britta Kohlbrecher; Christian Merkl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2022)
This paper shows that a search and matching model with idiosyncratic training cost shocks can explain the asymmetric movement of the job-finding rate over the business cycle and the decline of matching efficiency in recessions. Large negative aggregate shocks move the hiring cutoff into a part of the training cost distribution with higher density. The position of the hiring cutoff in the distribution is disciplined by the empirical elasticity of the job-finding rate with respect to market tightness. Our model explains a large fraction of the matching efficiency decline during the Great Recession and generates state-dependent effects of policy interventions.
Keywords: E24; E32; J63; J64; 330; Business cycle asymmetries; matching function; Beveridge curve; job-finding rate; unemployment; effectiveness of policy